2013
DOI: 10.1007/s12221-013-1301-2
|View full text |Cite
|
Sign up to set email alerts
|

Compressive viscoelastic properties of softwood kraft lignin-based flexible polyurethane foams

Abstract: Softwood kraft lignin (SKL)-based water-blown flexible polyurethane foams were prepared using SKL as a crosslinking agent and a hard segment polyol. Polyethylene glycol (PEG) as a soft segment diol and 2,4-toluene diisocyanate (TDI) were used. While increasing hard segment content caused the increase in crosslink density in foams, the foams became more and more viscous with increasing hard segment content due to the distinctive phase heterogeneity in foams. In this case, the contributiveness of the filler-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
(43 reference statements)
0
22
0
Order By: Relevance
“…Oxypropylated lignins have been incorporated into rigid PU foams at 5–100 wt % loading with “comparable performance” to control foams [15,70,94,102]. The incorporation of modified lignins into rigid PU foams has been reported to improve biodegradation [103], compressive strength [104,105,106], tensile strength [107], thermal conductivity [108], thermal degradation [109], and anti-flaming properties [110] compared to control foams. In some cases it is also reported to increase density [106], cell size [84], and cell irregularity [88] of the foams.…”
Section: Lignin-based Polyurethanesmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxypropylated lignins have been incorporated into rigid PU foams at 5–100 wt % loading with “comparable performance” to control foams [15,70,94,102]. The incorporation of modified lignins into rigid PU foams has been reported to improve biodegradation [103], compressive strength [104,105,106], tensile strength [107], thermal conductivity [108], thermal degradation [109], and anti-flaming properties [110] compared to control foams. In some cases it is also reported to increase density [106], cell size [84], and cell irregularity [88] of the foams.…”
Section: Lignin-based Polyurethanesmentioning
confidence: 99%
“…Lignin incorporated into flexible PU foams can act as both a filler [119] and crosslinking agent (by reacting with an isocyanate) [106]. Previous studies have used either unmodified lignins [95,106] or chemically modified lignins [120,121,122] to partially replace (6–30 wt %) the polyol portion of flexible PU foams. The thermal stability and mechanical properties foams prepared using modified lignins were reported to increase by increasing lignin content [120,121,123].…”
Section: Lignin-based Polyurethanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that lignins have useful rheological and viscoelastic properties to develop a structural material, 16,24,33 meaningful film forming ability, 31,33,34 and compatibility with a wide range of solvents. 23,24,34 Lignins are multifunctional biopolymers that carry many aliphatic hydroxyl and phenolic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The lignin macromolecule is mainly composed of phenyl propane structures (Jeong et al 2013). Many chromophoric groups are present the molecule, such as phenolic hydroxyl, quinone structures, and carbonyl (Fjellström et al 2008).…”
Section: Brightness Vs Kappa Numbermentioning
confidence: 99%